Homovanillic acid and 5-hydroxyindole acetic acid as biomarkers for dementia with Lewy bodies and coincident Alzheimer’s disease: An autopsy-confirmed study - Morimoto, Satoru (PLoS One, 2017)
Dementia with Lewy bodies (DLB) and Alzheimer’s disease (AD) are the two most common causes of dementia. Both pathologies often coexist, and AD patients with concomitant neocortical LB pathology (referred to as the Lewy body variant of AD) generally show faster cognitive decline and accelerated mortality relative to patients with pure AD. Thus, discriminating among patients with DLB, AD, and coincident DLB and AD is important in clinical practice. We examined levels of homovanillic acid (HVA), 5-hydroxyindole acetic acid (5-HIAA), tau, phosphorylated tau (p-tau), and beta-amyloid (Aβ) 1–42 in cerebrospinal fluid (CSF) to evaluate their viability as biomarkers to discriminate among different forms of dementia. We obtained a total of 3498 CSF samples from patients admitted to our hospital during the period from 1996 to 2015. Of these patients, we were able to carry out a brain autopsy in 94 cases. Finally, 78 neuropathologically diagnosed cases (10 AD, six DLB, five DLB with AD, five controls without neurological diseases, and 52 cases with other neurological diseases) were studied. CSF levels of HVA and 5-HIAA were consistently decreased in pathologically advanced Lewy body disorder (LBD; Braak LB stages >3) compared with pathologically incipient LBD (Braak LB stages <2). These results suggest that if an individual has LB pathology in the central nervous system, CSF levels of HVA and 5-HIAA may decrease after the onset of clinical symptoms. In addition, CSF levels of HVA and 5-HIAA decreased with LB pathology, and were especially low in cases of DLB and DLB with AD. Furthermore, the combination of HVA, 5-HIAA, and brain specific proteins t-tau, p-tau, and Aβ 1–42 in CSF were useful for discriminating among DLB, DLB with AD, and AD with high diagnostic accuracy.